2022
DOI: 10.1002/marc.202200118
|View full text |Cite
|
Sign up to set email alerts
|

Cibalackrot Dendrimers for Hyperfluorescent Organic Light‐Emitting Diodes

Abstract: Hyperfluorescent organic light-emitting diodes (HF-OLEDs) enable a cascading Förster resonance energy transfer (FRET) from a suitable thermally activated delayed fluorescent (TADF) assistant host to a fluorescent end-emitter to give efficient OLEDs with relatively narrowed electroluminescence compared to TADF-OLEDs. Efficient HF-OLEDs require optimal FRET with minimum triplet diffusion via Dexter-type energy transfer (DET) from the TADF assistant host to the fluorescent end-emitter. To hinder DET, steric prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Adachi and Shih et al in 2022 reported the first HF-OLEDs based on dendrimers, which were macromolecules with highly defined structures. 107 The dendrimers' showed a high solubility in most of the organic solvents and it was due to the addition of fresh, highly twisted dendrons to a cibalackrot core. Dendrimer mixed films were used to create HF-OLEDs that had EQE greater than 10% at 100 cd m −2 .…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…Adachi and Shih et al in 2022 reported the first HF-OLEDs based on dendrimers, which were macromolecules with highly defined structures. 107 The dendrimers' showed a high solubility in most of the organic solvents and it was due to the addition of fresh, highly twisted dendrons to a cibalackrot core. Dendrimer mixed films were used to create HF-OLEDs that had EQE greater than 10% at 100 cd m −2 .…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…Following this, the singlet excitons were transferred to FIrpic and rubrene, respectively, via Förster resonance energy transfer (FRET). [37][38][39] The singlet excitons in FIrpic converted to triplets rapidly through efficient intersystem crossing (ISC) thanks to the Ir atom for improving the spin-orbital coupling. Finally, the triplet excitons decayed to the ground state for a blue phosphorescent emission.…”
Section: Device Structure Of White Oletsmentioning
confidence: 99%
“…[17,18] But unfortunately, a primary undesirable energy loss channel, dexter energy transfer (DET) from the triplet state of TADF to the dark triplet state of the emitter, still exists in the HF-OLEDs that adversely affect the device's performance. [19,20] Hyperfluorescent organic light-emitting diodes (HF-OLEDs) approach has made it possible to achieve excellent device performance and color purity with low roll-off using noble-metal-free pure organic emitter. Despite significant progress, the performance of HF-OLEDs is still unsatisfactory due to the existence of a competitive dexter energy transfer (DET) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,18 ] But unfortunately, a primary undesirable energy loss channel, dexter energy transfer (DET) from the triplet state of TADF to the dark triplet state of the emitter, still exists in the HF‐OLEDs that adversely affect the device's performance. [ 19,20 ]…”
Section: Introductionmentioning
confidence: 99%